PERFORMANCE MANAGEMENT SYSTEM AND STRATEGIC CONTROLS THROUGH STAKEHOLDERS’ EYES - Dr. Leviticus M. Barazon, Jr. & Dr. Niña Jen R. Canayong (International Journal of Research Science and Management, 2019)
Perception is considered as an important factor in the implementation of the performance management system. The process of translating efforts to results requires analysis of the current perceived realities that surround its implementation. Hence, an investigation has been conducted in the relationship of these two variables. A thematic analysis of the current perception is used using semi-structured interview. The results show differences in how they implement their strategic controls based on their perceived essence on the performance management system. Important implications are derived on how to strengthen the strategic controls by shifting how somebody perceives the essence of the performance management system. Variations in the perception have shown corresponding variations on how they implement their strategic controls. It is concluded that perception of school leaders have a direct impact on the kind of strategic controls they implement.